A health economic analysis of the management of open lower limb fractures in the elderly - Pley, Caitlin (Eur J Orthop Surg Traumatol, 2020)
AIM: The aim of this study was to investigate the financial implications of the inpatient management of open lower limb fractures in adults over 65 years old. Further, the study compares the calculated cost to the income received by the hospital for these patients and to the existing body of literature. METHODS: This study employed direct inpatient costing analysis to estimate the cost of treating the open lower limb fractures incurred by 58 patients over the age of 65 years treated in our centre (Addenbrooke's Hospital, Cambridge University Hospitals NHS Trust) between March 2014 and March 2019. RESULTS: The median cost of inpatient care calculated in this study was £20,398 per patient, resulting in a financial loss to the hospital of £5113 per patient. When the results were disaggregated by sex, the median cost for an open lower limb fracture in a male patient was £20,886 compared to £19,304 in a female patient. Data were also disaggregated by the site of injury, which produced a median cost for an open femur fracture of £23,949, and £24,549 and £15,362 for open tibia and ankle fractures, respectively. CONCLUSION: This study provides a valuable estimate of the expense of treating open lower limb fractures in patients over the age of 65 years in a Major Trauma Centre in England. The study highlights the large losses incurred by hospitals in treating these cases, and supports revision of the remuneration structures in the National Health Service to adequately cover their cost.